“DON’T LET ME GO”. A CASE STUDY ON MUSIC THERAPY IN EARLY-STAGE DEMENTIA - VĂDUVA, Lois; WARNER, Catherine (Studia Universitatis Babes-Bolyai Musica, 2021)
This case study presents the process of music therapy in a clinical setting, under the professional supervision of Dr. Catherine Warner, a music therapist with over 25 years of experience in this field. The music therapy sessions were conducted with a client displaying early-stage dementia symptoms. Over twelve weeks, with an eight-week hiatus due to the Covid-19 Pandemic lockdown, the client benefited from music therapy sessions which helped her navigate through the challenges of the disease, as well as providing a safe environment to express feelings and emotions. This case study presents the main themes of the work, such as combining poetry with singing, and listening to soothing music. This paper also illustrates the challenges of the sessions, especially in relation to memory loss and anxiety. Lastly, the therapist’s reflections are presented to complete the overview of the work. Rezumat. "NU MĂ LĂSA SĂ PLEC”. UN STUDIU DE CAZ PE MUZICOTERAPIE ÎN DEMENȚĂ INCIPIENTĂ. Acest studiu de caz prezintă procesul muzicoterapeutic într-un cadru clinic, condus sub supravegherea profesională a Dr. Catherine Warner, muzicoterapeut cu experiență de peste 25 de ani în domeniu. Sesiunile de muzicoterapie au avut loc cu un client care prezintă simptome de demență în stadiu incipient. Timp de douăsprezece săptămâni, cu o pauză de opt săptămâni din cauza pandemiei Covid-19, clientul a beneficiat de sesiuni de muzicoterapie care au ajutat-o ​​să navigheze provocările bolii, și i-au oferit un mediu de siguranță pentru a-și exprima sentimentele și emoțiile. Acest studiu de caz prezintă principalele teme ale lucrării, cum ar fi îmbinarea dintre poezie și cântare, dar și ascultarea unei muzici liniștitoare. Această lucrare ilustrează, de asemenea, provocările sesiunilor, în special în ceea ce privește pierderea memoriei și anxietatea. În cele din urmă, reflecțiile terapeutului sunt prezentate pentru a completa imaginea de ansamblu a acestor sesiuni. Cuvinte cheie: muzicoterapie, demență, traumă, cântat